Aspectos demográficos y económicos del consumidor de productos importados y su relación sectorial en la ciudad de Machala - Carrión Asunción, Nilda Elizabeth (2015)
This research project is aimed at investigating the behavior of the consumer of imported vehicles in the city of Machala, through an investigation that will enable the design of sales strategies to trading companies of these goods, the methodology of research is run using the technique of survey that will allow a quantitative approach in such a way that you can get accurate information and relevant for optimal results, this aspect of being feasible to perceive the different needs. At present the demands of the consumers are much more complex, in their desires and needs that you have, the more even though it is the case of vehicles are so specific in their purchases by the interest that has, for the expectations that expects to receive, for the reasons, by the attributes, the reasons for purchase, by the preference, the uncertainties that they are concerned about the buy, it is more have become experts by the constant evolution of the growth of competition, of the variety of products or services, the processes of loyalty that has each brand that is to say but will offer you something different than the conventional, simply search for someone do it for you, it is for this reason that we have to meet to the Customers in what they want or need. In the automotive sector Ecuador has a very important participation remains one of the main productive sectors of the country due to the volume of sales, today, the automotive industry is being developed to run different requirements as well as the developments that are of the hand with the conservation and protection of the nature, advancing new technologies, effectively and less pollution to the environment. Because of this, you should design marketing strategies to achieve the market share in the concessionaires of vehicles and increase sales.